Sugar cane spirits: cachaca and rum production and sensory properties - Faria, J. B.; Piggott, J. (Woodhead Publ Ltd, 2012)
The production of cachaca, a distilled spirit made directly from sugar cane juice and rum obtained by fermenting molasses, a by-product of the sugar industry, are comparatively presented. The main differences, from raw material to fermentation, distillation and aging process are pointed out, in order to explain the resulting composition and distinct sensory characteristics of these two beverages and to show the importance of the sensory quality control, during all the production process.
Keywords: cachaca; rum; sugar cane; molasses; fermentation; distillation; sensory quality control